Advances in Understanding and Managing Refeeding Syndrome: A Comprehensive Review - Agata Mazur; Aleksy Bizan; Natalia Dąbrowska; Aleksandra Kublińska; Magdalena Madera; Krzysztof Marcinkowski; Sylwia Mazur; Emilia Nagórska; Karolina Strus; Roksana Zdunek (Nicolaus Copernicus University in Toruń, 2024)
BACKGROUND: Refeeding syndrome (RFS) is a potentially serious complication that can occur during the reintroduction of nutrition in individuals who have experienced a period of malnutrition or starvation. The pathophysiology of RFS is multifaceted and primarily driven by shifts in electrolytes, fluids, and metabolic substrates, including phosphate, potassium and magnesium, as well as thiamine deficiency. RFS can be easily overlooked due to the wide range of clinical presentations, from asymptomatic electrolyte disturbance to multiorgan failure. It is vital to recognize the condition to identify at-risk patients and implement preventive measures. OBJECTIVES: This review article aims to increase awareness of refeeding syndrome, educate physicians and other healthcare professionals, especially those outside of nutrition support teams, and provide a concise overview of the existing knowledge and suggested guidelines regarding RFS. CONCLUSIONS: Although refeeding syndrome is potentially fatal, its occurrence is preventable. During the initial 2-5 days of increased calorie intake, it is crucial to monitor the concentrations of phosphate and other electrolytes, as well as to check for any new symptoms. The key components of RFS therapy include slow increases in feeding rates, phosphate and potassium replacement, fluid management, and thiamine supplementation. Further research is required on refeeding syndrome, including epidemiological studies, investigations into pathophysiology such as the role of magnesium, and large-scale randomized controlled clinical trials to establish a consensus on management.